2014
DOI: 10.1007/s11845-014-1191-3
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CT head in the acute setting: value of contrast and non-contrast studies

Abstract: Head CT in ED non-traumatic neurological presentations with CECTH is not generally indicated and represents a calculable cost savings in the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Studied literature indicated that administration of intravenous contrast does little to change the sensitivity of CTB findings. 1 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Studied literature indicated that administration of intravenous contrast does little to change the sensitivity of CTB findings. 1 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…36 However, in our systematic review, we found only 1 study that discussed the cost of CTH studies. 18 Computed tomographic studies are associated with significant radiation exposure and cancer risk. A single CT study's mean radiation dose is typically 15 mSv in adults and 30 mSv in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Overall, this process may also introduce delays in the reporting of the studies of other patients in the emergency department, thus increasing patient turnaround time and potentially leading to overcrowding, bed shortages, and a potential negative impact patient care. 49 -53…”
Section: Discussionmentioning
confidence: 99%